2007
DOI: 10.2754/avb200776040619
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Streptococcus canis Strains Isolated from Dogs and Cats

Abstract: To determine the prevalence of Streptococcus canis in dogs and cats, a total of 926 swabs were examined bacteriologically in the period from 2003 to 2005. Eighty-six isolates obtained from various anatomical locations were further characterized for their phenotypic properties. The most frequently isolated biotype produced phosphatase, leucine amidopeptidase, arginine dihydrolase, alpha-D-and beta-D-galactosidase and fermented lactose and ribose. Additional identification by species-specific amplification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 17 publications
(15 reference statements)
5
26
2
1
Order By: Relevance
“…After performing 16S rRNA PCR and gene sequencing, four isolates from healthy group were identified as Staphyloccus pseudintermedius (2 isolates), Bacillus cereus (1 isolate) and Staphylococcus shleiferi (1 isolate). These findings were in agreement with that of Lysková et al (2007) who reported isolation of Staphylcococcus spp., Bacillus spp. and Malassezia pachydermatis spp., in normal healthy canine ears.…”
Section: Microflora Identifiedsupporting
confidence: 93%
See 1 more Smart Citation
“…After performing 16S rRNA PCR and gene sequencing, four isolates from healthy group were identified as Staphyloccus pseudintermedius (2 isolates), Bacillus cereus (1 isolate) and Staphylococcus shleiferi (1 isolate). These findings were in agreement with that of Lysková et al (2007) who reported isolation of Staphylcococcus spp., Bacillus spp. and Malassezia pachydermatis spp., in normal healthy canine ears.…”
Section: Microflora Identifiedsupporting
confidence: 93%
“…They also reported that the Staphylococcus spp., were highly sensitive to chloramphenicol which was seen in our study. Lysková et al (2007) also reported sensitivity of Staphylococcus spp. and Pseudomonas spp., to gentamicin and ciprofloxacin.…”
Section: Antibiotic Sensitivity Of Bacterial Isolatesmentioning
confidence: 90%
“…In the case of uncomplicated skin infections, often only Staph. Beta-haemolytic streptococci have also been isolated from dogs with dermatitis (Lyskov a et al 2007;Lamm et al 2010). or Pseudomonas aeruginosa, may be present in addition to Staph.…”
Section: Introductionmentioning
confidence: 99%
“…pseudintermedius (Dowling 1996;Ihrke 2006). Beta-haemolytic streptococci have also been isolated from dogs with dermatitis (Lyskov a et al 2007;Lamm et al 2010). In ear infections, the major causative organisms beside yeasts are Staph.…”
Section: Introductionmentioning
confidence: 99%
“…() and S. dysgalactiae strains isolated from the human pharynx (Rantala, ; Woo, Fung, Lau, Wong, & Yuen, ). In contrast, Lysková, Vydržalová, Královcová, and Mazurová () found some S. canis strains with vancomicin resistance isolated to external ears canal, vaginal mucosa, pharynx and oral cavity, conjunctivae, skin and the rectum in dogs. Gianneechini et al.…”
Section: Discussionmentioning
confidence: 97%